Techniques of Problem Solving
The purpose of this book is to teach the basic principles of problem solving, including both mathematical and non-mathematical problems. Taking a direct and practical approach to the subject matter, Krantz’s book stands apart from others like it in that it incorporates exercises throughout the text. Additional problems are included for readers to tackle at the end of each chapter. There are more than 350 problems in all. A Solutions Manual to most end-of-chapter exercises is available.